Is Latin America on the Right Track? An Analysis of Medium-Term Frameworks and the Budget Process - Carlos Scartascini; Gabriel Filc (Inter-American Development Bank (IDB), 2010)
Medium Term Fiscal Frameworks (MTFs) have become one of the most popular reforms to the budgetary process in Latin America during the last decade, and introducing MTFs seemed to be the magic solution for most fiscal ailments. Nonetheless, there has been no comprehensive evaluation of their impact. This document discusses the normative merits of using MTFs, provides a characterization of the different types of MTF, and describes their development in the Latin American region based on extensive field work. As a first approximation for understanding how they are working, this document explores in detail the cases of Argentina, Colombia and Peru. While an unambiguous diagnosis is not possible, this document lays the groundwork for progress toward comprehensive impact evaluations and, eventually, to the consolidation of MTFs in the region.
Keywords: H61; H68; H00; 330; Latin America; Medium-Term Fiscal Frameworks; Medium-Term Expenditure Frameworks; Budget Process; Fiscal Outcomes; Fiscal Reforms